GANTI RUGI KORBAN KECELAKAAN LALU LINTAS PERSPEKTIF HUKUM POSITIF DAN FIKIH MAZBAB ( STUDI KASUS POLRES BONE) - Laman, Ilham (Citra Media Publishing, 2024)
Traffic accidents always cause losses, losses are a state of diminishment of a benefit possessed by a person, losses can be material or immaterial. From this background, three formulations of the problem are given birth, namely, how is the compensation for victims of traffic injury from a positive legal perspective.? secondly how is the compensation for victims of traffic accidents from the perspective of the Shafi'I school and its relevance in the Bone Police.? thirdly how is the settlement of compensation in the Bone Police? The research method uses field research with qualitative descriptive research methods. Descriptive research is a study that aims to describe the nature, facts and relationships between the phenomena studied. The purpose of qualitative descriptive research is to produce descriptive data in the form of images, words, of the observed behavior of the community. The researcher will immediately conduct interviews, observations for information. The results showed that, first in the Law. No.22 of 2009 concerning Road Traffic and Transportation, if a family peaceful road cannot be carried out then this matter is resolved in court. Secondly, compensation for victims of traffic accidents from the perspective of the shafi'I school and its relevance in the Bone Police, compensation is called diyat in islamic law and is obliged to pay and predominantly paid with camels at that time while its relevance in the Bone Police is the same as obliging to compensate for the negligence of the perpetrator even though the payment method is different from the perspective of the school because at that time the camel was the most privileged animal that could be given to the victim. Third, in the settlement of compensation in the police department, there were 426 cases of compensation for traffic accidents that occurred in 2021 where the settlement was peaceful or familial (not brought to justice) with material damages by interpreting the damages incurreds